Assessment of PD-L1 mRNA expression in gastrointestinal tumors and the response to immunotherapy - Qiu, Qingqing; Li, Jieyi; Chen, Qiaofeng; Zhao, Xiaokai; Zhou, Ru; Zhang, Wenpeng; Gong, Ziying; Zhang, Daoyun; Wang, Mingliang (Frontiers in Oncology, 2022)
Background: Programmed death-ligand 1 (PD-L1) immunohistochemistry (IHC) has been proposed as a predictive biomarker to predict response to immunotherapy. Given the limitations of IHC test in PD-L1 detection, this study aimed to investigate the technical feasibility of using quantitative RT-PCR (qRT-PCR) to replace IHC in PD-L1 detection in gastrointestinal tumors. Materials and Methods: The TCGA database was used to evaluate the relationship between PD-L1 expression in tumor tissue and the patient prognosis. Also, 52 patients with gastrointestinal cancer were enrolled and divided into the stomach (STAD), colon (COAD), and rectum (READ) adenocarcinoma cohort. IHC test was used to determine the PD-L1 level of the tissue specimens, and the qRT-PCR test was used to analyze the mRNA expression in both blood and tissue specimens. Besides, the correlation between blood PD-L1 mRNA expression and immunotherapy efficacy was investigated in additional 15 gastric cancer patients that further enrolled. Results: The expression level of PD-L1 in tumor tissue is related to the tumor stage of COAD (p-value = 0.001) and primary therapy outcomes in patients with READ (p-value = 0.003), but not significantly correlated to the overall survival (OS) time of gastrointestinal cancer patients. Besides, the concordance of PD-L1 mRNA expression level of tissue and paired blood samples is low, despite a weak linear relationship that was found in the STAD cohort (r = 0.43, p-value = 0.049). We further demonstrated that qRT-PCR results in both tissue and blood specimens were numerically but not statistically significant consistent with IHC results (corresponding to a p-value of 0.84 and 0.55, respectively). Remarkably, high-expressed PD-L1 in blood of STAD patients shows a better response to immunotherapy (p-value = 0.04), which could well-identified at the relative expression cut-off of 1.5 (85.7% sensitivity, 75.0% specificity, AUC = 0.82).